Breeding habitats, phenology and size of a resident population of Two‐banded Plover (Charadrius falklandicus) at the northern edge of its distribution. (26th June 2021) - Faria, Fernando A.; Repenning, MÁrcio; Tavares Nunes, Guilherme; Senner, Nathan R.; Bugoni, Leandro
Abstract: The central‐peripheral hypothesis states that the demographic performance of a species decreases from the centre to the edge of its range. Peripheral populations are often smaller and tend to occur under different and suboptimal conditions from those of core populations. Peripheral populations can also coexist during part of their annual cycle with populations from the core of the species' range. Studies on peripheral populations are thus valuable for broadly understanding ecological and evolutionary processes. The Two‐banded Plover (TWBP, Charadrius falklandicus, Charadriidae) is an endemic South American shorebird that breeds in Argentine and Chilean Patagonia and migrates northward during the Austral winter. There are breeding records, however, from Lagoa do Peixe National Park in southern Brazil. In this study, we (i) mapped TWBP nests, (ii) characterised their reproductive biology and nesting habitats, (iii) colour‐marked birds and evaluated their seasonal occurrence patterns and (iv) estimated the size of the Brazilian population by combining supervised habitat classification analyses and generalised additive models. We estimated that the Brazilian population has 55 (95% CI: 44.1–66.6) breeding pairs and found that the length of their breeding season was roughly 5 months, spanning the Austral spring and summer. The population's nesting habitat differed, and their apparent reproductive success was lower than that of core populations. Unlike more southerly populations, the results of our mark‐resighting efforts demonstrate that the Brazilian population is sedentary. Taken together, these results indicate that the Brazilian TWBP population seems geographically isolated from the species' southernmost core populations, resulting in a heteropatric distribution. Furthermore, differences in nesting habitat and year‐round residency indicate that this peripheral population is ecologically distinct. The marked behavioural and ecological differences combined with the small population at the northern edge of the TWBP distribution support the central‐peripheral hypothesis in a Neotropical system. Portuguese: A hipótese centro‐periferia estabelece que a performance demográfica de uma espécie diminui do centro para os extremos de sua distribuição. Populações periféricas são frequentemente menores e tendem a ocorrer em condições subótimas quando comparadas com populações centrais. Populações periféricas podem ainda coexistir durante parte do seu ciclo anual com populações do centro da distribuição da espécie. Estudos com populações periféricas são, portanto, cruciais para uma ampla compreensão de processos ecológicos e evolutivos. A Batuíra‐de‐coleira‐dupla ( Charadrius falklandicus, Charadriidae) é uma espécie de ave costeira endêmica da América do Sul, que se reproduz na Patagônia argentina e chilena, e migra para o norte durante o verão austral. No entanto, existem registros de sua reprodução no Parque Nacional da Lagoa do Peixe, no sul do Brasil. Nesse estudo, nós (i) mapeamos ninhos da espécie, (ii) caracterizamos sua biologia reprodutiva e habitat de nidificação, (iii) marcamos individualmente aves e avaliamos seu padrão de ocorrência sazonal, e (iv) estimamos o tamanho da população brasileira através da combinação de análises de classificação supervisionada de habitat e modelos aditivos generalizados. Estimamos que a população brasileira possui 55 pares reprodutivos (IC95%: 44, 1 – 66, 6) e que o período de reprodução foi de, aproximadamente, 5 meses, abrangendo a primavera e verão austrais. O habitat de nidificação da população diferiu e o sucesso reprodutivo aparente foi menor quando comparado às populações centrais. Diferentemente das populações mais austrais, os resultados de esforços de marcação e recaptura demonstraram que a população brasileira é sedentária. A combinação desses resultados sugere que a população brasileira da Batuíra‐de‐coleira‐dupla está geograficamente isolada das populações austrais, resultando em distribuição heteropátrica. Além disso, o habitat de nidificação e o padrão sedentário indicam que essa população periférica é ecologicamente distinta. As diferenças comportamentais e ecológicas, combinadas com o pequeno tamanho populacional na Lagoa do Peixe, no limite norte da distribuição da Batuíra‐de‐coleira‐dupla, suportam a hipótese centro‐periferia em um sistema Neotropical.